ANTIOBESITY ACTIVITITY OF WATER FRACTIONS EXTRACT OF TAMARIND (TAMARINDUS INDICA L.) IN HIGH CARBOHYDRATE DIET INDUCED MALE WISTAR RATS - Hidayah, Nurul; Adnyana I, Ketut; Fisheri, Neng; Setiawan, Finna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The prevalence of obesity increases each year globally. Multifactorial etiology of obesity requires therapy management including changing of diet and medicines. Some of obesity drugs have shown ineffectiveness and safety. The previous study showed that water extract of tamarind could reduce body weight (bw). This study aimed to test the activity fraction of water extract tamarind as antiobesity using high carbohydrate diet. Method: The preventive research of antiobesity had done by given water fraction and ethyl acetate fraction of water extract tamarind following with induced high carbohydrate diet during 6th weeks in male Wistar rats. The parameters had observed including consumption of food, body weight, weight of feces, volume of urine, total cholesterols, triglycerides, blood glucose, index of organs, and accumulation of body fat. Result: The ethyl acetate fraction at doses 4.5 mg/kg bw has shown significantly effect to decrease of total cholesterols level and decrease of triglycerides level at weeks 6 (p<0.05). All the tests of fraction have shown activity inhibition of increased body weight, decrease of appetite, total cholesterols, triglycerides, and blood glucose. Meanwhile, mechanism action of antiobesity as increase defecation, urination, and decrease index of organs and accumulation of body fat have not shown by all these test fractions. Conclusion: The ethyl acetate fraction at doses of 4.5 mg/kg bw can inhibit raising of body weight, decrease of total cholesterols, and triglycerides level greater than the other test groups, where increasing of these levels of blood biochemistry was closely related to the pathology of obesity.